2018
DOI: 10.3892/ijmm.2018.3969
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol suppresses colon cancer growth by targeting the AKT/STAT3 signaling pathway

Abstract: colon cancer is a common type of cancer worldwide and accounts for a significant number of cancer-related deaths. Although surgical techniques and treatment strategies for colon cancer have advanced over the past two decades, the prognosis has not improved considerably. Resveratrol, a natural stilbene compound, possesses antioxidant, cardioprotective and anticancer properties. However, the role of resveratrol in colon cancer has not been fully elucidated. The present study demonstrated that resveratrol inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 38 publications
0
47
0
Order By: Relevance
“…Resveratrol is considered to be a promising anticancer drug for chemoprevention or therapy for colon cancer, targeting numerous cellular molecules, such as AKT serine/threonine kinase 1 (AKT1), AKT2 [19], and AKT/GSK-3β/Snail signaling pathway [20], and increasing ROS production [21]. In the current study, RSV at a dose of 6 µ g/implant significantly reduced the tumor weight of s.c. (subcutaneously)-implanted COLO205-luc in athymic mice.…”
Section: Discussionmentioning
confidence: 64%
“…Resveratrol is considered to be a promising anticancer drug for chemoprevention or therapy for colon cancer, targeting numerous cellular molecules, such as AKT serine/threonine kinase 1 (AKT1), AKT2 [19], and AKT/GSK-3β/Snail signaling pathway [20], and increasing ROS production [21]. In the current study, RSV at a dose of 6 µ g/implant significantly reduced the tumor weight of s.c. (subcutaneously)-implanted COLO205-luc in athymic mice.…”
Section: Discussionmentioning
confidence: 64%
“…In summary, these data suggested that RV retards melanoma growth in an autophagy-dependent manner through the inhibition of PI3K/AKT/mTOR signaling. Previous studies have similarly reported that RV can potentially prevent various malignancies through inhibiting cellular proliferation and regulating autophagy (22)(23)(24). In a study by Lei et al (25), RV decreased proliferation, enhanced cellular differentiation and improved melanin generation in HT-144 melanoma cells through inhibiting the mitogen-activated protein kinase kinase/ERK kinase pathway.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have shown that resveratrol inhibits IL-6induced transcriptional activity of STAT3 in human prostate cancer LNCaP-FGC cells (18), and STAT3 axis in primary glioblastoma tumor initiating cells (19). Inhibition of STAT3 signaling plays a critical role in resveratrol-induced suppression of several types of cancer, including ovarian cancer (20,21), pancreatic cancer cells (22), head and neck tumor cells (23), osteosarcoma (24), colorectal cancer (25), colon cancer (26). In these types of cancers, it has been shown that resveratrol inhibits STAT3 Tyr705 phosphorylation (22)(23)(24)(25)(26) and STAT3 S727 phosphorylation (23,25).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of STAT3 signaling plays a critical role in resveratrol-induced suppression of several types of cancer, including ovarian cancer (20,21), pancreatic cancer cells (22), head and neck tumor cells (23), osteosarcoma (24), colorectal cancer (25), colon cancer (26). In these types of cancers, it has been shown that resveratrol inhibits STAT3 Tyr705 phosphorylation (22)(23)(24)(25)(26) and STAT3 S727 phosphorylation (23,25). Zhang et al showed that STAT3 signaling is more critical for cervical cancer cells and is the major target of resveratrol because selective inhibition of STAT3 rather than Wnt or Notch activation commits SiHa and Hela cells to apoptosis (27).…”
Section: Introductionmentioning
confidence: 99%